Pengaruh Konsentrasi Asam Stearat dan Suhu Gelatinisasi terhadap Karakteristik Komposit Bioplastik Tapioka dan Glukomanan - Damanik, Jhon Berry Finn; Harsujuwono, Bambang Admadi; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
This study aims to determine the effect of stearic acid concentration and gelatinization temperature and the interaction of the two treatments on the characteristics of tapioca and glucomannan bioplastic composites, and determine the concentration of stearic acid and gelatinization temperature which can produce bioplastic composites with the best characteristics. This study used a randomized block design with two factors. The first factor is the concentration of stearic acid which consists of 0.2%, 0.4%, 0.6%, 0.8%. The second factor is the gelatinization temperature which consists of 4 temperatures, namely 70±1°C, 75±1°C, 80±1°C, 85±1°C. The variables observed in this study were tensile strength, elongation at break, elasticity, thickness expansion, water vapor transmission rate, biodegradation and functional group analysis. The data were analyzed for diversity and continued with Duncan's Multiple Comparison. The results showed that the concentration of stearic acid and gelatinization temperature had a very significant effect on tensile strength, thickness expansion, water vapor transmission rate and biodegradation. The interaction between treatments had a very significant effect on tensile strength, thickness expansion, water vapor transmission rate and biodegradation and significantly affected elongation at break and elasticity. The best tapioca and glucomannan bioplastic composites used a stearic acid concentration of 0.4% and a gelatinization temperature of 80±1°C which had the characteristics of a tensile strength of 23.86 MPa, elongation at break 8 .70%, elasticity 274 .40 MPa, thickness expansion 111 .52%, water vapour transmission rate 1 .05 g/m2.hour, biodegradation rate with 7 days old. Tapioca and glucomannan bioplastic composites contain functional groups of hydroxyl (O-H), alkyne (C?H), aldehyde (C=O), carboxylic acid (C-O), alkene (C-H) and hydroxyl hydrocarbon (CH 2 )n. Keywords : bioplastic composite, tapioca, glucomannan, stearic acid, gelatinization temperature